Processed 2 minutes-averaged continuous VM-ADCP (vessel-mounted Acoustic Doppler Current Profiler) profiles during POLARSTERN cruise PS98 - Hannelore Witte; Bernhard Pospichal (PANGAEA, 2018)
This data set was collected during the R. V. Polarstern cruise PS98. Outside territorial waters, current velocities were measured nearly continuously along the ship extquotesingles track with a vessel-mounted TRD Instruments 153.6-kHz Ocean Surveyor ADCP. The transducers were located 11 m below the water line and were protected against ice floes by an acoustically transparent plastic window. The current measurements used a pulse of 2 seconds and vertical bin length of 4 meters. The ship extquotesingles velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Heading, roll and pitch data from the ship extquotesingles gyro platforms and the navigation data were used to convert the ADCP velocities into earth coordinates. The accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the ship extquotesingles heading data. Further errors stem from a misalignment of the transducer with the ship extquotesingles centerline. The ADCP data were processed using the Ocean Surveyor Sputum Interpreter (OSSI) software developed by GEOMAR Helmholtz-Zentrum für Ozeanforschung Kiel. The reference layer was set to avoid near surface effects. The averaging interval was set to 120 seconds. Sampling interval setting: 2s; Number of bins: 80; Bin length: 4m; Pulse length: 4m; Blank beyond transmit length: 4m. Data processing setting: Upper depth of reference layer: 30m; Lower depth of reference layer: 80m; Time average: 120s; Misalignment angle: 0.900; amplitude: 1.0240. The precision for single ping and 4m cell size reported by TRDI is 0.30m/s. Resulting from the single ping precision and the number of pings (most of the time 36) during 120seconds the velocity accuracy is nearly 0.05m/s. (Velocity accuracy = single ping precision divided by square root of the number of pings)